A sustainable approach on tax audit inspection: How tax aggressive strategies can be detected from fee of independent auditor - Rachmad Miftachul Arifuddin (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2023)
The problem with self-reporting data is that taxpayers can be mindful in declaring their tax returns. In some cases, they may intentionally select information on the financial statement for taxation purposes. Tax audits are an essential tool for this problem, but the coverage ratio for corporate enterprises needs to be higher. Increasing the coverage might be one solution to enforce compliance since tax audits require lots of resources. Directorate General of Taxation (DGT) should consider that some variables may influence a taxpayer’s behavior and then use them in the tax audit program. This paper will discuss how the fee of an independent auditor might affect the tendency to perform tax-aggressive strategies. The analysis looks at 22,519 audited financial reports from Indonesian businesses. The paper will employ Instrument Variables to address the endogeneity issue in the dataset. The finding indicates that audit fees harm tax-aggressive strategies. Thus, audit fee data could predict an audited enterprise’s behavior. The result from this IV estimator can be used as an insight by DGT in determining their tax audit strategy.